2018
DOI: 10.1371/journal.pone.0193997
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with patient and health system delays in diagnosis and treatment of tuberculosis in Montenegro, 2015–2016

Abstract: BackgroundFundamental measures of control of tuberculosis are early detection and timely treatment of the affected. The aim of this study was to identify factors associated with patient-related and health system-related delays among patients with tuberculosis in the Republic of Montenegro.MethodsA cross-sectional study included 130 tuberculosis patients older than 15 years of age. The inclusion criteria were diagnosis of tuberculosis based on clinical, pathohistological and microbiological findings. Patient de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
4
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 14 publications
7
19
4
5
Order By: Relevance
“…Since TB is a potentially lethal highly infectious disease, and by the time most patients are treated, they have already infected many others, even one day longer delay in diagnosis could be harmful for both patient and public health. Time delays in diagnosis of TB are often reported as total delay, patient delay, and health system delay [ 23 , 24 ]. While a recent systematic review about time delays in diagnosis of pulmonary TB demonstrated that the reported average patient delay was similar to health system delay (28.7 versus 25 days) [ 25 ], Nasehi et al showed that a large part of the delay from onset of symptoms to diagnosing TB in Iran was related to the health care system (and not the patient), which was the same as our result.…”
Section: Discussionmentioning
confidence: 99%
“…Since TB is a potentially lethal highly infectious disease, and by the time most patients are treated, they have already infected many others, even one day longer delay in diagnosis could be harmful for both patient and public health. Time delays in diagnosis of TB are often reported as total delay, patient delay, and health system delay [ 23 , 24 ]. While a recent systematic review about time delays in diagnosis of pulmonary TB demonstrated that the reported average patient delay was similar to health system delay (28.7 versus 25 days) [ 25 ], Nasehi et al showed that a large part of the delay from onset of symptoms to diagnosing TB in Iran was related to the health care system (and not the patient), which was the same as our result.…”
Section: Discussionmentioning
confidence: 99%
“…However, many TB patients are not promptly diagnosed; instead, they remain ill and contagious for a long period of time before the detection of the cause while many were not even diagnosed before they died (17). Diagnosis is usually at the advanced stages of the TB disease when complications must have set in which is usually due to patient's remedy-seeking behavior, ill-suited diagnostic investigation requested by a clinician, and unsatisfactory capacities for error-free diagnosis at the available health care facilities (26)(27)(28). In Africa, the diagnosis of TB depends mainly on microscopically detecting culprit acidfast bacilli (with inconsistent gram stain color) in the patient's sputum, which is an insensitive technique especially among HIV seropositive individuals, who have not many bacilli in their sputum and are prone to more complications such as extra pulmonary tuberculosis as com-pared to HIV seronegative patients (17).…”
Section: Late Diagnosis and Insensitive Technique Of Tb Detectionmentioning
confidence: 99%
“…In another multi-centre study of mortality associated with misdiagnosis, the researchers reported misdiagnosis in 11.6% (113/974) patients with 15% in-hospital mortality. 7 In some other instances, it is not uncommon for treatment to commence later than is required for the most efficient clinical intervention as a result of inadequate testing facilities, 8 delays in diagnosis of disease 9 and slow diagnostic process. 10 For instance, the use of stool culture in the diagnosis of Clostridium difficile diarrhoea takes 2-3 days to complete, thereby delaying commencement of treatment.…”
Section: Introductionmentioning
confidence: 99%